Effect of hot-iron brand size and meloxicam on behavior, health, and performance of beef calves in a pasture setting - Keogh, Lily, author; Edwards-Callaway, Lily, advisor; Cramer, Catie, advisor; Wolfe, Barb, committee member; Engle, Terry, committee member (Colorado State University. Libraries, 2024)
Animal welfare is of growing importance in beef cattle production and therefore there is heightened interest in regularly practiced, painful management practices. Hot-iron branding is a common method of permanent identification of cattle, created by intense thermal damage to the hide. The main objectives of the study were to quantify the effects of hot-iron brand size and meloxicam on pain related behaviors and health and performance parameters of 2-month-old beef calves on a commercial cow calf operation. A total of 126 calves were enrolled in the study (bulls, n=56; heifers, n=70). Calves were hot-iron branded with one of two iron sizes (small (SM), large (LG)) and administered meloxicam (MEL; dosed for a 113-kg calf at 1mg/kg of bodyweight) or a placebo (PLA)), and castrated (CAS) or not castrated (NCAS), if a heifer calf. Following the treatment application, behavioral observation (2 h periods) using instantaneous scan sampling occurred at 6 h and 24 h post branding; these observation periods (OP) represent the pharmacokinetics of oral meloxicam. A logistic regression (PROC GLIMIX) was used to assess the association between castration status, brand size, medication, observation period, as well as any interactions, on the proportional behavioral outcomes. More LG brand calves were observed standing, lying, and displaying event behaviors as compared to the SM brand calves (P = 0.003, P = 0.011, P = 0.016, respectively). OP affected the display of event and state behaviors, with standing observed more at 6 h and event behaviors displayed more at 24 h (P = 0.0028). Concurrently, CAS and SM or LG branded calves exhibited more event behaviors and standing than NCAS calves (P = 0.022). No effect of the fixed variables on average daily gain (ADG) or morbidity were observed (P > 0.05). MEL did reduce the proportion of branded heifer calves expressing event behaviors as compared to PLA, however it had less of a behavioral impact on the concurrently castrated and branded calves (P = 0.022). The results indicate that pain is present within the 24 h following branding and castration and that concurrent castration and branding elicits a greater behavioral response than only branding. This study highlighted both the feasibility of administering an oral analgesic in a commercial setting and that implementing a smaller brand size may be a strategy to reduce pain associated with hot-iron branding.
Keywords: calves; hot-iron branding; pasture; castration; behavior; NSAID